2011
DOI: 10.1590/s1413-81232011000700094
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e fatores associados a sobrepeso e obesidade em escolares da rede pública

Abstract: Prevalência e fatores associados a sobrepeso e obesidade em escolares da rede públicaPrevalence and factors associated to overweight and obesity in public schools

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0
23

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 16 publications
4
5
0
23
Order By: Relevance
“…The nutritional profile of students from public schools in Juiz de Fora (MG) with a mean age of 10.8 years was also similar to that of the present sample given that 7.5% and 10.4% of the women were overweight and obese, respectively, and 13.5% and 7.6% of the men were overweight and obese, respectively 30 .…”
Section: Discussionsupporting
confidence: 79%
“…The nutritional profile of students from public schools in Juiz de Fora (MG) with a mean age of 10.8 years was also similar to that of the present sample given that 7.5% and 10.4% of the women were overweight and obese, respectively, and 13.5% and 7.6% of the men were overweight and obese, respectively 30 .…”
Section: Discussionsupporting
confidence: 79%
“…Cases were more likely than controls to have overweight or obese parents. This association was expected, since it has been reported by Brazilian and foreign studies 18,19,[26][27][28] . Although the data suggest a genetic component, parental nutritional status may be an indicator of environmental characteristics shared with children, such as food habits and level of physical activity, both of which can be important risk factors for overweight.…”
Section: Discussionsupporting
confidence: 61%
“…Like other studies, the study overweight/ obese third-graders are more likely to use passive Revista de Nutrição http://dx.doi.org/10.1590/1678-98652016000300010 school transport 27,30 . Recent studies have found that active school transport was predictive of lower BMI 39 and increased child cardiovascular endurance during physical activity 40 ; thus, active school transport seems like an important strategy for the promotion of physical activity and prevention of childhood overweight.…”
Section: Discussionmentioning
confidence: 75%
“…The accumulation of body fat present in children of school age tends to persist into adolescence, which has physiological and pathological effects in adult life too. For this reason, the characteristics as a risk group and the chances of success for the actions to be implemented cause overweight adolescents to be one of the main target-groups for strategies of prevention and control of overweight and illnesses correlated with it, based on primary healthcare (PHC) (2) .…”
Section: Introductionmentioning
confidence: 99%